2001
DOI: 10.1097/00005792-200101000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic Manifestations of Infective Endocarditis in Non-Addicts

Abstract: Infective endocarditis (IE) is due to a microbial infection of the heart valves or of the endocardium in close proximity to either congenital or acquired cardiac defects. This infection is associated with a high risk of complications. Rheumatic manifestations are known to be frequent complications of IE. Controversy, however, frequently exists about the actual incidence of these complications. This may be due to the small number of series describing the frequency and type of rheumatic manifestations, the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1
13

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 21 publications
0
44
1
13
Order By: Relevance
“…Progress in bacteriological research has enabled new studies to publish more cases of septic arthritis occurring in the course of an IE [7] [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in bacteriological research has enabled new studies to publish more cases of septic arthritis occurring in the course of an IE [7] [8].…”
Section: Discussionmentioning
confidence: 99%
“…There is no correlation between joint damage and the affected valve [8] [10]- [12]. Some studies reported no significant difference in the distribution of isolated germ according to the presence or absence of rheumatic manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathologic findings were consistent with leukocytoclastic cutaneous vasculitis (LCV). As previously reported, LCV related to bacterial infection was considered if no drug intake was registered before the development of skin lesions, and bacteriologic evidence of infection was obtained [1]. In cases with IE and LCV, a trend to low serum complement levels was evident.…”
Section: Discussionmentioning
confidence: 99%
“…Infective endocarditis (IE) is due to a microbial infection of the heart valves or of the endocardium in close proximity to either congenital or acquired cardiac defects [1]. In a patient with a murmur and a fever of undetermined origin, precipitating or predisposing factors, if present, should produce a high index of suspicion of infective endocarditis [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation